Study on Model of Heat and Moisture Transfer of Fractal Polyesters (Journal of Fiber Bioengineering and Informatics, 2012)
The dynamic moisture absorption of fractal polyester was studied at a constant temperature (30 °C) andhumidity (80% RH). The model of heat and moisture transfer was then built based on the heat andmass transfer theories. Finite element method was used to solve the model. By comparing the moistureabsorption predicted by the mechanism model and the experimental data, we concluded that variationstrend of both were consistent. Besides, fields of temperature and humidity with different thickness offractal polyester were predicted and analyzed by this model.